2023
DOI: 10.1039/d3nr04619b
|View full text |Cite
|
Sign up to set email alerts
|

Sn-doped ZnO for efficient and stable quantum dot light-emitting diodes via a microchannel synthesis strategy

Ting Wang,
Liming Xie,
Fuyan Su
et al.

Abstract: Microchannel synthesis of Sn-doped ZnO with uniform size distribution for constructing efficient and stable QLEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This increased PL intensity of the encapsulated micro-LEDs may be attributed to the passivation of the defect sites on the surface of green QDs and the anti-reflection effect of the prepared thin films. 42 As shown in Fig. 4d, during thermal cycling tests involving three cycles alternating between room temperature and 250 °C, the micro-LEDs encapsulated with PEALD SiO 2 and T-ALD Al 2 O 3 exhibited QD fractures, whereas the micro-LEDs encapsulated with SA 2/1 maintained undamaged QDs.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…This increased PL intensity of the encapsulated micro-LEDs may be attributed to the passivation of the defect sites on the surface of green QDs and the anti-reflection effect of the prepared thin films. 42 As shown in Fig. 4d, during thermal cycling tests involving three cycles alternating between room temperature and 250 °C, the micro-LEDs encapsulated with PEALD SiO 2 and T-ALD Al 2 O 3 exhibited QD fractures, whereas the micro-LEDs encapsulated with SA 2/1 maintained undamaged QDs.…”
Section: Resultsmentioning
confidence: 85%
“…This increased PL intensity of the encapsulated micro-LEDs may be attributed to the passivation of the defect sites on the surface of green QDs and the anti-reflection effect of the prepared thin films. 42 As shown in ted QD fractures, whereas the micro-LEDs encapsulated with SA 2/1 maintained undamaged QDs. When the encapsulated micro-LEDs were exposed to damp heat conditions (60 °C, 90% RH) for one week, the surface of the micro-LEDs encapsulated with PEALD SiO 2 and T-ALD Al 2 O 3 developed a white dot, whereas the surface of SA 2/1 remained unchanged.…”
Section: Resultsmentioning
confidence: 91%
“…In Fig. 1(b)-(e), the O 1s core-level signal is deconvoluted into two peaks at around 529.6 and 531.2 eV, 17,34 which can be attributed to the lattice oxygen and oxygen vacancies. It was found that the intensity of oxygen vacancies in the modified ZnO was significantly reduced compared to the pristine ZnO, suggesting that the oxygen atoms on the sulfonate molecules tend to be adsorbed on the surface of ZnO NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Among various metal oxide ETLs, ZnO nanoparticles (NPs) are highly favored due to their high electron mobility, optimal band alignment, holeblocking capability, low sensitivity to humidity, and low synthesis cost. [14][15][16][17] Although ZnO NPs can be used as ETLs, their outstanding capabilities may lead to imbalanced charge transport in QLEDs. It is reported that the accumulation of excess electrons at the HTL/emission layer (EML) interface can result in charging the QDs and intensify non-radiative Auger recombination.…”
Section: Introductionmentioning
confidence: 99%